First seroprevalence survey of bovine anaplasmosis: an emerging tick-borne disease in commercial livestock and dairy farms in Bangladesh - Md. Makshuder Rahman Zim; Nurnabi Ahmed; Mostak Ahmed; Md. Abu Haris Miah; Md. Mahfuzur Rahman Sajib; Md. Rajiur Rahaman Rabbi; Md. Khalilur Rahman; Babul Chandra Roy; Md. Hasanuzzaman Talukder; Ala Tabor (Parasitology)
Bovine anaplasmosis is an infectious, tick-borne disease caused by Anaplasma species, which is accountable for huge economic loss in dairy industry. This study was aimed to determine the seroprevalence of bovine anaplasmosis on randomly selected 61 commercial dairy farms in 3 intensive regions of Bangladesh. A total of 1472 sera were analysed using VMRD Anaplasma Antibody Test Kit cELISA v2 for the presence of Anaplasma-specific antibodies. The highest regional seroprevalence of Anaplasma was 45.93% in individual level and 74.4% in herd level recorded in the southeast region, whereas it was 48.8% in individual level and 83.3% in herd level in Khagrachari and Sherpur districts, indicating an emerging state of the disease. The herd size and type in herd level and regions, districts, sex, age and breed in individual level were significantly (P ≤ 0.05) associated with anaplasmosis. Multivariate logistic regression analysis showed that cattle aged >1 year had 1.86 times higher odds compared to cattle younger than 1 year. Dairy cows had the highest odds (2.25) of anaplasmosis, followed by dairy heifers (1.68), compared to bulls. Compared to herd sizes of <4, the odds of Anaplasma infection were 11.3 and 7.45 times greater in herd sizes of >28 and 4–28. Crossbred cattle had 2.4 times higher odds of anaplasmosis compared to indigenous cattle. This first seroprevalence study signifies the widespread presence and underscores the importance of monitoring and managing anaplasmosis to safeguard cattle health in Bangladesh. Study on the molecular epidemiology and genetic diversity of Anaplasma among cattle populations should be prioritized.